Monovalent Omicron COVID-19 vaccine triggers superior neutralizing antibody responses against Omicron subvariants than Delta and Omicron bivalent vaccine - Wanting Li; Tiantian Zhao; Bai Tao; Liwei Zhao; Hang Xiao; Xinyu Ding; Chuang Li; Lin Chen; Hao Cheng; Yang Lou; Yuxin Chen; Chao Wu (Taylor & Francis Group, 2023)
The continuous evolution of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants poses a challenge to determine the optimal updated composition of the coronavirus disease 2019 (COVID-19) vaccine. The present study aimed to investigate the immunogenicity of the Delta monovalent vaccine, the Omicron monovalent vaccine, and the Delta and Omicron BA.1 bivalent vaccine. Three COVID-19 vaccines were designed using the heterologous DNA prime-protein boost strategy, with each vaccine containing either Delta receptor-binding domain (RBD) of the spike protein, Omicron RBD, or both Delta and Omicron antigens. Temporal serum antibody binding titers and neutralizing antibody titers induced by the three vaccines in New Zealand White rabbits were analyzed. To further dissect the vaccine elicited antibodies (mAb) responses at the molecular level, a panel of rabbit monoclonal antibodies (RmAbs) was generated by a high-throughput single B cell sorting and discovery pipeline and further comprehensively characterized. The Omicron monovalent vaccine induced higher antibody binding titers and neutralization activities than the Delta and Omicron bivalent vaccine. Four RmAbs with robust neutralization capacity were isolated from rabbits immunized with the Omicron or Delta monovalent vaccine. Notably, 9E11 isolated from the Omicron monovalent vaccine group neutralized all the Omicron subvariants with an IC50 value ranging from 1.5 to 503.6 ng/mL; thus, this vaccine could serve as a prophylactic and therapeutic intervention. Given the increasing incidence of COVID-19 cases due to the Omicron variant, RBD from the Omicron strain could serve as a candidate immunogen that can induce higher neutralization activities against the SARS-CoV-2 Omicron sublineages.